MANAJEMEN KESISWAAN BERBASIS KESEJAHTERAAN: EVALUASI PROGRAM MAKAN BERGIZI GRATIS DAN KESIAPAN BELAJAR SANTRI DI PONDOK PESANTREN MA’RIFATULLAH DESA SUNGAI ULAK KECAMATAN NALO TANTAN - Edi Wardani; Muslimah; Darni; Edi Putra Jaya; Dina Puspita. D (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of the Free Nutritious Meal Program (Program Makan Bergizi Gratis / MBG) as an instrument of welfare-based student management and its contribution to students’ learning readiness at Ma’rifatullah Tahfidz Al-Qur’an Islamic Boarding School, Sungai Ulak Village, Nalo Tantan District. This study employed a mixed methods approach using the CIPP evaluation model (Context, Input, Process, Product). Data were collected through observation, in-depth interviews, documentation, and questionnaires involving pesantren administrators, teachers, food program managers, and students as program beneficiaries. Qualitative data were analyzed through data reduction, data display, and conclusion drawing, while quantitative data were analyzed descriptively to identify students’ learning readiness levels. The findings reveal that the MBG program functions not only as a food provision service but also as an integral component of welfare based student management. The program is implemented through collaborative governance involving all elements of the pesantren and contributes to improving students’ physical conditions, concentration, learning motivation, discipline, and engagement in educational activities. This study proposes a conceptual model of welfare-based student management that integrates nutritional services, program governance, student well-being, learning readiness, and the improvement of Islamic boarding school educational quality. These findings contribute to the development of Islamic education management by positioning student welfare services as a strategic element in enhancing educational quality.